Dining in the dark - Spence, C; Piqueras-Fiszman, B (2012)
The last decade or so has seen the steady rise of the 'Dine-in-the-dark' or 'Dans le noir' restaurant, where diners pay to eat and drink in complete darkness. Why are these restaurants popular? Addressing this question requires consideration of several others, such as: Does food really taste better in the dark? And, does dining in the dark provide any meaningful insight into how the blind experience food and drink? This article argues that it is the constant feeling of surprise, based on the delivery of unusual sensory experiences, that may really make such dark dining experiences so unusual and intriguing for the customers.